Implementasi Program Perbantuan Lapangan Perizinan Berusaha Berbasis Online Single Submission Bagi Usaha Mikro, Kecil, Dan Menengah Di Kabupaten Tabanan - Kadek Putri Gayatri; I Dewa Ayu Putri Wirantari; Putu Nomy Yasintha (CV. Lenggogeni Data Publishing, 2023)
The OSS-Based Business Licensing Field Assistance Program is one of the strategies that aims to make it easier for MSME actors to manage business license. This program is carried out with a ball pickup system to each village with the services served focusing on assistance in registering business permits through OSS. In this study, the author used a type of qualitative research with a descriptive method. The analysis in this study uses implementation theory from Charles O. Jones. The research findings show that the implementation of the program has run well but has not been fully optimized. It is seen that there are indicators that are still not met, including the shortcomings of the number of OSS operators, not yet established maximum coordination from stakeholders, socialization that is not optimal, does not have a fixed schedule, and system errors.